JavaScript JSON cookbook: over 80 recipes to make the most of JSON in your desktop, server, web, and mobile applications - Rischpater, Ray (Quick Answers to Common Problems, 2015)
About This BookCreate fast and dynamic JavaScript applications that implement JSONPractical examples to show you how to leverage JSON from a variety of application domainsBecome the go-to person for building JSON-enabled web applications in your organizationWho This Book Is ForIf you're writing applications that move structured data from one place to another, this book is for you. This is especially true if you've been using XML to do the job because it's entirely possible that you could do much of the same work with less code and less data overhead in JSON.While the book's chapters make some distinction between the client and server sides of an application, it doesn't matter if you're a frontend, backend, or full-stack developer. The principles behind using JSON apply to both the client and the server, and in fact, developers who understand both sides of the equation generally craft the best applications.